The primary solution : rescuing our democracy from the fringes - Troiano, Nick (Simon & Schuster, 2024)
"In a divided America, the biggest solvable problem fueling political extremism and dysfunction is hiding in plain sight: partisan primaries. The Primary Solution shows how to fix them"--Dust jacket flap.